Industri Perbankan Syariah Dan Kondisi Ekonomi Makro Di Indonesia - Dian Anggraini; Maya Panorama (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2021)
Islam is a universal religion that has the Qur'an as a way of life. Universal here is not limited by time and place. The Qur'an which was revealed by Prophet Muhammad SAW regulates all aspects of human life. The purpose of this study is to identify and examine the Islamic banking industry and macroeconomic conditions in Indonesia. The method used is multiple regression analysis with estimation of Ordinary Least Squares (OLS). The results of this study indicate that economic activity is an aspect that has become a concern since the emergence of Islam. Islamic banking at this time has a very rapid growth that is strongly influenced by macroeconomics in obtaining its goal of getting the highest profit. The variables studied are financial ratios that are adjusted to the decision of Bank Indonesia and accompanied by the MUI Fatwa influenced by CAR, FDR and BOPO. Each change in ROA can be explained through the variables CAR, FDR and BOPO of 82.9% while the remaining 17.1% is influenced by other factors).